Online Pornography among Student in Semarang City: The Influence of Attitudes and Subjective Norms - Magumi Avrora Iftita; Kismi Mubarokah (Journal of Educational, Health and Community Psychology, 2024)
Pornography, as erotic content, can stimulate sensual desire and is accessible through various mediums, including viewing, reading, listening, and watching. Teenagers are particularly vulnerable to the dangers of digital pornography. This study aims to examine the influence of attitudes and subjective norms on students' intentions to consume online pornography in Semarang City. A quantitative approach was employed, involving 1,319 student participants from various educational levels. The data were analyzed using ordinal logistic regression. The results indicate that both independent variables significantly impact the dependent variable. Student attitudes exert the most substantial influence, with an Odds Ratio of 4.32, while subjective norms have an Odds Ratio of 2.13. The study concludes that attitudes and subjective norms together significantly affect the intention to consume online pornography.